Youth Bulges, Insurrections, and Politico-Economic Institutions - Lena Gerling; Thomas Apolte (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We develop a model of insurrection markets and integrate the youth bulge as measured by the relative youth cohort size. As youth-specific characteristics we define the young person's attitude toward revolutionary groups and the government, the degree of risk aversion and the relative productivity of young people on the insurrection market as compared to the official labor market. We find that, apart from certain spontaneous outbreaks of violence or riots, youth bulges alone are not a good predictor for political violence. Nevertheless, deliberate insurrection activities that aim at changing political and economic power positions are indeed affected by youth bulges, but indirectly so, and their intensity is driven by the characteristics of the respective underlying set of politico-economic institutions. We test our implications in an empirical model based on cross-country panel data and find that the effect of the relative youth cohort size on insurrection outbreaks is moderated by changes in the underlying institutional setting, and more precisely changes in the labor-market conditions as approximated by unemployment rates.
Keywords: H56; J10; J22; 330